Forgiveness and Personal Peacefulness among High School Adolescents: A Correlational Study - Mutia Tasya Khoiri; Anandha Putri Rahimsyah; Gian Sugiana Sugara (Journal of Mental Health and Well-Being in Counseling, 2026)
Forgiveness and personal peacefulness are two essential indicators of positive mental health, supporting adolescents’ capacity to adapt to academic, social, and emotional demands. This study aimed to examine the relationship between personal peacefulness and forgiveness among high school students. A cross-sectional quantitative design with a correlational approach was applied, involving 359 adolescents selected through purposive sampling. Personal peacefulness was assessed using the standardized Self Perception Scale (SPS), while forgiveness was measured using the Heartland Forgiveness Scale (HFS). The findings revealed a significant positive correlation between personal peacefulness and forgiveness (r = 0.593), with the dimensions of self-forgiveness and situational forgiveness contributing most substantially to multiple aspects of personal peacefulness. These results confirm that adolescents with higher forgiveness capacities toward self, others, and adverse situations tend to report greater levels of personal peacefulness. Overall, this study emphasizes the importance of developing forgiveness-based and positive psychology interventions within school guidance and counseling services to foster adolescents’ mental well-being.